Krisis Identitas Perempuan dalam Bab “The Problem That Has No Name” pada Buku The Feminine Mystique Karya Betty Friedan dalam Perspektif Al-Qur'an - Arya Pandji Pratama; Rakha Muhammad Hafizh; Adya Abiyyu Dharma; Nabila Sadida; Dadan Firdaus (Indo Publishing, 2026)
This study aims to analyze women's identity crisis in the chapter The Problem That Has No Name by Betty Friedan using Erik Erikson's theory and a Qur'anic perspective. This qualitative study employed library research and content analysis methods. The findings reveal that women experience loss of self-identity, self-doubt, and difficulties in finding meaning in life. The crisis is influenced by social factors, limited opportunities for self-development, and pressures of feminine ideals. From a Qur'anic perspective, QS. An-Nahl [16]: 97 and QS. An-Nisa' [4]: 32 emphasize the importance of self-development and recognition of individual efforts.